Evaluation of the impact of the ecological environment damage compensation system on enterprise pollutant emissions - Li, Zhaoyang; Li, Yisong (Frontiers in Environmental Science, 2025)
The development of an environmental damage compensation framework is a critical innovation in ecological civilization reforms. This study considers the pilot policy for environmental damage compensation reform as a quasi-natural experiment, employing a difference-in-differences approach with emission data from listed companies between 2008 and 2017. The research evaluates the environmental impact of the compensation system’s implementation in pilot areas and its implications for improving environmental legal practices. The results show that the compensation system significantly reduces corporate pollution emissions by 1.93% (p < 0.01), demonstrating its effectiveness as an environmental governance tool. The heterogeneity analysis reveals stronger effects in heavily polluting industries (3.30%, p < 0.01) compared to non-heavily polluting industries (1.25%, p < 0.1), in state-owned enterprises (2.06%, p < 0.01) versus non-state-owned enterprises (1.71%, p < 0.1), and in developed regions (2.50%, p < 0.01) compared to underdeveloped areas (1.00%, not significant). The dual mechanisms of negotiation and litigation in the compensation system impose strict constraints on corporate environmental behavior, effectively addressing the issue of “corporate pollution, public suffering, and government expenses.” To optimize the system, targeted policy recommendations include strengthening negotiation mechanisms, refining judicial responsibilities, and enhancing coordination in underdeveloped regions. These findings highlight the originality and importance of the compensation framework as a model for balancing ecological protection and economic development.